(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Online classes, like face-to-face classes, need effective management so that they do not get out of the teacher’s control and students have valuable and meaningful learning. Undoubtedly, the teacher has an effective role in teaching the student, and successful online classes are the result of a set of common roles and responsibilities between the teacher and the students. The purpose of this study was to investigate the problems of online classroom management and the methods and strategies used by novice and experienced teachers and to review the most appropriate techniques for planning and refining effective online and teamwork topics and discussing time and volume management strategies. Work and issues related to the online environment. For this purpose, the researcher has used a qualitative method and observing classes and semi-structured interviews used as instrumentsin this research. The results of this study showed that the professional development of online education, especially in the field of classroom management, requires a set of practical strategies, knowing how to communicate well with students, and having an effective classroom management program, managing asynchronous discussions and online teamwork. The results of this study can be useful for teachers, especially novice teachers, in effectively managing online classrooms and increasing learning opportunities for all students, from disruptive behaviors, which is often very important because these are often the main components of online learning. Prevent in class and provide solutions for better online learning.